2021
DOI: 10.48550/arxiv.2104.12070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking the evolution of lithium in giants using asteroseismology: Super-Li-rich stars are almost exclusively young red-clump stars

Raghubar Singh,
Bacham E. Reddy,
Simon W. Campbell
et al.

Abstract: We report novel observational evidence on the evolutionary status of lithium-rich giant stars by combining asteroseismic and lithium abundance data. Comparing observations and models of the asteroseismic gravity-mode period spacing ∆Π 1 , we find that super-Li-rich giants (SLR, A(Li) > 3.2 dex) are almost exclusively young red-clump (RC) stars. Depending on the exact phase of evolution, which requires more data to refine, SLR stars are either (i) less than ∼ 2 Myr or (ii) less than ∼ 40 Myr past the main core … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…The recent discovery of large samples of Li-rich giants indicates that they are not restricted just to the luminosity bump on the RGB for the low-mass stars, or its equivalent on the early-AGB for intermediate mass stars that ignite central He burning in nondegenerate conditions (Charbonnel & Balachandran 2000), but they are also found along the RGB and in the red clump (see, e.g Alcalá et al 2011;Kumar et al 2011;Lebzelter et al 2012;Carlberg et al 2016;Smiljanic et al 2018;Deepak & Reddy 2019;Charbonnel et al 2020;Martell et al 2020;Yan et al 2021). The works of ; Yan et al (2021); Singh et al (2021); Deepak & Lambert (2021), combining the results from asteroseismic and spectroscopic surveys, suggested that a high fraction of the Li-rich giants belong to the red clump central He-burning phase, confirming a previous idea presented by Kumar et al (2011). Similar results were obtained by Casey et al (2019) where 80% of their sample stars have likely helium-burning cores.…”
Section: Lithium-rich Giant Stars and Their Evolutionary Statussupporting
confidence: 55%
“…The recent discovery of large samples of Li-rich giants indicates that they are not restricted just to the luminosity bump on the RGB for the low-mass stars, or its equivalent on the early-AGB for intermediate mass stars that ignite central He burning in nondegenerate conditions (Charbonnel & Balachandran 2000), but they are also found along the RGB and in the red clump (see, e.g Alcalá et al 2011;Kumar et al 2011;Lebzelter et al 2012;Carlberg et al 2016;Smiljanic et al 2018;Deepak & Reddy 2019;Charbonnel et al 2020;Martell et al 2020;Yan et al 2021). The works of ; Yan et al (2021); Singh et al (2021); Deepak & Lambert (2021), combining the results from asteroseismic and spectroscopic surveys, suggested that a high fraction of the Li-rich giants belong to the red clump central He-burning phase, confirming a previous idea presented by Kumar et al (2011). Similar results were obtained by Casey et al (2019) where 80% of their sample stars have likely helium-burning cores.…”
Section: Lithium-rich Giant Stars and Their Evolutionary Statussupporting
confidence: 55%